Mental fatigue over 2 elite netball seasons: a case for mental fatigue to be included in athlete self-report Mmasures - Russell, S.; Jenkins, D. G.; Halson, S. L.; Juliff, L. E.; Connick, M. J.; Kelly, V. G. (International Journal of Sports Physiology and Performance, 2022)
Purpose: Mental fatigue is emerging as an important consideration for elite sporting performance, yet it is rarely monitored. The present study assessed changes in mental fatigue in professional team-sport athletes across 2 seasons and examined the relationship between mental fatigue and other athlete self-report measures of well-being.